PENINGKATAN PRODUKTIVITAS DAN KUALITAS PALM SUGAR DARI NIRA AREN DI KECAMATAN NOKILALAKI KABUPATEN SIGI - Abdul Rahim, Arifuddin Lamusa, Abd. Hamid, Abdul (AGROTEKBIS, 2015)
The activities carried out in the group Tongoa Aren in the village of Tongoa and Mandiri Bulili in the village of Bulili of District Nokilalaki Sigi with the aim to increase were productivity and the quality of palm sugar from aren juice with the processing technology that can be applied to a group of business partners. The method used to achieve the goals and objectives are counseling, training and mentoring of aren juice processing technology in a controlled manner into palm sugar. The results showed that the target audience activity can be improved productivity and the quality of palm sugar from aren juice with the controlled processing technologies ranging from the preparation of materials and equipment, processing to the packaging. Prior to the program IbM 2015, a group of farmers aren cultivate aren juice into sugar printing sell Rp 12,500, - per kg, after following this program can produce palm sugar and sell it for Rp 30,000, - per kg, so that with the program IbM can increase the income and welfare of farmers aren mainly target farmers' groups.